2020
DOI: 10.1186/s12933-020-01171-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum Cyr61 levels with peripheral arterial disease in subjects with type 2 diabetes

Abstract: Background The prevalence of peripheral artery disease (PAD) is obviously increased in patients with diabetes. Existing evidence shows that cysteine-rich angiogenic inducer 61 (Cyr61), a 40-kD secreted protein, plays important roles in regulating cellular physiological processes. Recent studies have demonstrated a significant correlation between serum Cyr61 and atherosclerosis. However, the relationship between Cyr61 levels and PAD in patients with type 2 diabetes (T2DM) remains obscure. Methods Data from a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
2
5
0
1
Order By: Relevance
“…Our data demonstrated a noteworthy correlation between CCN1 and the duration of diabetes, in keeping with findings from the study by Bin Feng et al [ 60 ] and Zhao-Yu Xiang et al [ 61 ]. Notably, we have provided new and compelling evidence, showcasing elevated levels of circulating CCN1 in DR patients presenting with hard exudates.…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrated a noteworthy correlation between CCN1 and the duration of diabetes, in keeping with findings from the study by Bin Feng et al [ 60 ] and Zhao-Yu Xiang et al [ 61 ]. Notably, we have provided new and compelling evidence, showcasing elevated levels of circulating CCN1 in DR patients presenting with hard exudates.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that the levels of exosomal Cyr61 were significantly associated with sex, family history of ACS and glucose levels in patients with ACS. Similar patterns were also observed in a study by Feng et al (34), in which Cyr61 was significantly associated with the risk of peripheral artery disease in both the crude and adjusted models, including age, sex, diabetes duration, fasting glucose and hypertension. In addition, a previous study has demonstrated that serum Cyr61 levels were positively correlated with CRP levels in coronary artery disease (23).…”
Section: Discussionsupporting
confidence: 88%
“…Previous reports have shown that CCN1 expression is increased in the retinas from mice with DM and from patients with DR, as well as in the vitreous humor of patients with PDR ( 15 , 16 , 44 ). Furthermore, circulating CCN1 levels are significantly correlated with the severity of peripheral arterial disease in diabetic patients ( 45 ). Other studies have shown that CCN1 regulates VEGF signaling during DR progression ( 17 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, circulating CCN1 levels are significantly correlated with the severity of peripheral arterial disease in diabetic patients ( 45 ). Other studies have shown that CCN1 regulates VEGF signaling during DR progression ( 17 , 45 ). Those studies suggest a possible role of CCN1 in the pathogenesis of DR.…”
Section: Discussionmentioning
confidence: 99%